The role of alternative polyadenylation in breast cancer - Qiao, Ping; Zhang, Caihong; Shi, Yingxu; Du, Hua (Frontiers in Genetics, 2024)
Breast cancer (BC), as a highly prevalent malignant tumor worldwide, is still unclear in its pathogenesis and has poor therapeutic outcomes. Alternative polyadenylation (APA) is a posttranscriptional regulatory mechanism widely found in eukaryotes. Precursor mRNA (pre-mRNA) undergo the APA process to generate multiple mRNA isoforms with different coding regions or 3'UTRs, thereby greatly increasing the diversity and complexity of the eukaryotic transcriptome and proteome. Studies have shown that APA is involved in the progression of various diseases, including cancer, and plays a crucial role. Therefore, clarifying the biological mechanisms of APA and its regulators in breast cancer will help to comprehensively understand the pathogenesis of breast cancer and provide new ideas for its prevention and treatment. different coding regions and 3' UTRs for a single gene (Tian and Manley, 2017) . This posttranscriptional regulatory mechanism, called alternative polyadenylation (APA), increases the complexity and diversity of the transcriptome and proteome.With the development of sequencing technology and genomic analysis methods, the mechanism of APA's role in cancer has received extensive attention (Yuan et al., 2021). Recent studies have shown that APA regulation and the different transcriptional isoforms generated by it are involved in various aspects of tumorigenesis and development. In addition, aberrant expression of factors regulating APA leads to disruption of the APA process, which in turn affects cancer progression. Breast cancer, as one of the cancers threatening women's health, is closely related to abnormal APA regulation. Therefore, elucidating the biological mechanisms of APA and its regulatory factors in breast cancer will help to comprehensively understand the pathogenesis of breast cancer and provide new ideas for its prevention and treatment.